Risk factors associated with lymph node metastasis in papillary thyroid cancer: a retrospective analysis based on 2,428 cases - Yu, Kejie; Wu, Xianjiang; Dai, Lei; Le, Qi; Xie, Yue; Wang, Yingchun (Frontiers in Oncology, 2024)
BackgroundPapillary thyroid cancer (PTC) with lymph node metastasis (LNM) is associated with an increased risk of postoperative recurrence. Understanding the clinical characteristics of PTC patients can help surgeons assess the likelihood of LNM. This study aims to identify risk factors for LNM in PTC patients.MethodsWe retrospectively analyzed clinical data from 2,428 patients diagnosed with PTC who underwent initial thyroid surgery in our single center. Risk factors related to central lymph node metastasis (CLNM), lateral lymph node metastasis (LLNM), and skip metastasis were investigated by univariate and multivariate binary logistic regression analyses.ResultsUnivariate analysis revealed that the following factors were associated with an increased likelihood of CLNM (P<0.05): male gender, age < 45 years, maximal axial diameter (MAD) > 1 cm, body mass index (BMI) ≥ 28 kg/m² and multifocality. Univariate analysis also revealed that patients with age < 45 years, MAD > 1 cm, BMI ≥ 28 kg/m², multifocality, and CLNM demonstrated a higher propensity for LLNM (P<0.05). Lower pole tumors were more likely to have CLNM than upper pole tumors, while upper pole tumors were more prone to present LLNM (P<0.05) and skip metastasis (P<0.05). Multivariable binary logistic regression analysis identified that gender (odds ratio [OR], 1.732; 95% CI, 2.113–2.577; P < 0.001), age (OR, 1.905; 95% CI, 1.596–2.273; P < 0.001), MAD (OR, 4.639; 95% CI, 3.639–5.913; P < 0.001), and multifocality (OR, 1.860; 95% CI, 1.453–2.381; P < 0.001) were independent risk factors for CLNM and MAD (OR, 5.289; 95% CI, 3.777–7.404; P<0.001), multifocality (OR, 1.858; 95% CI, 1.248–2.766; P=0.002), and CLNM (OR, 5.030; 95% CI, 3.347–7.561; P<0.001) for LLNM.ConclusionDespite the overall postoperative recurrence rate in PTC patients is low, identifying risk factors such as male gender, age < 45 years, MAD > 1 cm, multifocality, and CLNM can help predict LNM. In specific cases, selective lymphadenectomy in the central or lateral neck area may be warranted.